Eye trauma during sports - K. Videnlieva; S. Kyuchukova (Trakia Journal of Sciences)
Eye trauma call any organ damage eyesight under the influence of adverse factors - mechanical, thermal, chemical.Despite the fact that the eye is well protected from orbit and eyelids, eye injuries during sports, feature prominently among eye diseases.This in turn can be a cause of irreversible vision loss.